1993
DOI: 10.1038/362345a0
|View full text |Cite
|
Sign up to set email alerts
|

Different binding epitopes on the NK1 receptor for substance P and a non-peptide antagonist

Abstract: Non-peptide ligands for peptide receptors have been discovered in several systems through file screening programs, but the mechanism of action for these candidate drugs is obscure as they do not chemically resemble the native peptides. The compound CP 96345 is a high-affinity, non-peptide antagonist of the substance P (NK1) receptor, which is important in pain perception and neurogenic inflammation. Here we identify epitopes on the NK1 receptor responsible for the specific binding of CP 96345 by systematic exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(105 citation statements)
references
References 22 publications
6
99
0
Order By: Relevance
“…This idea has been supported by a recent molecular pharmacological study using H/x chimeric receptors reported by Wang et al [18]. They revealed that substitution of the second extracellular loop of/I-OPR for the corresponding region of x-OPR increased the affinity for dynorphin A [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] by about 100-fold. In this study, we demonstrated that DAMGO distinguished between/1-and x-OPRs at the different region from that for the distinction between/1-and 6-OPRs.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…This idea has been supported by a recent molecular pharmacological study using H/x chimeric receptors reported by Wang et al [18]. They revealed that substitution of the second extracellular loop of/I-OPR for the corresponding region of x-OPR increased the affinity for dynorphin A [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] by about 100-fold. In this study, we demonstrated that DAMGO distinguished between/1-and x-OPRs at the different region from that for the distinction between/1-and 6-OPRs.…”
Section: Resultssupporting
confidence: 63%
“…The construction of chimeric receptors is thought to be one of the very powerful approaches to the issue, as it has been demonstrated in the cases of adrenaline [9,10], acetylcholine [11], tachykinin [12,13] and endothelin [14] receptors. Recently, using chimeric /~/~-OPRs, we have shown that DAMGO, a/I-OPR selective ligand, distinguishes between Hand 6-OPRs at the region around the first extracellular loop and that this region is partly involved in the discrimination between/l-and ~-OPRs also by other several peptidic/~-selective ligands, such as dermorphin, morphiceptin and CTOP, but not by non-peptidic ligands, such as morphine and naloxone [15].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that the region around the EL-1 is very critical just for DAMGO to distinguish between/~-and &-OPRs, while this region is partly involved in the subtype-specific binding of other peptidic g-selective ligands, but not in the discrimination between g-and 8-OPRs by non-peptidic ligands. These differences in the recognition sites for subtype-specific binding between DAMGO and other/,t-selective ligands are not so surprising, because it has been reported that the different ligands recognize the different sites of the same receptor in the cases of many receptors belonged to the G-protein coupled receptor family, such as fl-adrenergic, neurokinin-1 and ~-opioid receptors [5,13,14].…”
Section: Resultsmentioning
confidence: 99%
“…However, since we do not yet know the structural reason for the high constitutive activity of the ORF-74 receptor, it is far from evident that it should be possible to stop its signaling by binding of a small non-peptide ligand to its extracellular surface. Although there is general agreement that the binding sites for non-peptide ligands usually are significantly different from those for the endogenous peptide ligands (35,40,41), the molecular mechanism of action of non-peptide ligands is the subject of debate. One opinion is that the non-peptide antagonists act by blocking the binding of the agonist through a spacefilling process, although their binding sites may not overlap directly (42).…”
Section: Fig 6 Inhibition By Znmentioning
confidence: 99%